Experimental Study on Pathology of Aflatoxicosis in Broiler Chicks and Its Amelioration by Emblica officinalis (Amla) Supplementation - Khetmalis, R. S.; More, B. K.; Mote, C. S.; Jadhav, S. N.; Kamdi, B. P.; Dhaygude, V. S. (International Journal of Livestock Research, 2018)
An experiment was conducted to study the protective role of herb Emblica officinalis in induced aflatoxicosis in broilers. Thirty day old broiler chicks divided into three groups. Birds of group T0 were fed with standard basal rations. Group T1 birds were fed with standard feed mixed with aflatoxin (AF) B1@150 ppb and group T2 birds were fed with standard feed mix with AFB1@150 ppb and E. officinalis @5 g/kg of feed. Skin thicknesses were measured in six birds from each group on 21st day for cell mediated immune response. Group T1 and T2 showed significant differences in weight gain and significant reduction in cell mediated immune response was noted as compared to T0 group. Gross examination of group T1 birds showed yellowish discoloration of liver and hepatomegaly, mild lesions in kidneys. Microscopically, liver parenchyma showed moderate hepatic derangement, focal formation of microgranuloma, multiple foci of hepato-cellular swelling, necrosis in some hepatocytes, congestion of blood vessels, mononuclear cells infiltrations around blood vessels, focal bile duct hyperplasia and sinusoidal aggregation of erythrocytes. In T2 group birds, microscopically liver, kidney, spleen and bursa of Fabricius showed mild changes as compared to T1. Present study suggest that supplementation of herb E. officinalis could reduce aflatoxin toxicity in broilers.